A symmetric direct ammonia fuel cell using ternary NiCuFe alloy embedded in a carbon network as electrodes. Issue 36 (31st August 2022) - Zhang, Mengfei; Zhang, Jie; Jeerh, Georgina; Zou, Peimiao; Sun, Boyao; Walker, Marc; Xie, Kui; Tao, Shanwen
Abstract : This is the first report on a symmetric direct ammonia fuel cell (DAFC). Recently, due to the high energy density of carbon free fuel ammonia, low-temperature DAFCs have attracted extensive attention and play an important role in ammonia economy. Abstract : Recently, due to the high energy density of ammonia, low source-to-tank energy cost and carbon free fuel, low-temperature direct ammonia fuel cells (DAFCs) have attracted extensive attention and play an important role in ammonia economy. In DAFCs, Pt-based materials have been the most studied electrocatalysts for the anodic ammonia oxidation reaction (AOR) and cathodic oxygen reduction reaction (ORR) over the past decade. However, the high cost of precious metal has markedly inhibited the large-scale application of DAFCs. Herein, a bifunctional material of ternary Ni4Cu5Fe x ( x = 0, 0.5, 1, 3, 5) alloy embedded in a carbon network was prepared by a simple solvothermal approach, and showed superior activity and durability towards both AOR and ORR. The excellent bifunctional catalytic activity of the Ni4Cu5Fe1/C sample was analyzed by experimental and calculational methods. Utilizing the bifunctional activities of this alloy, a symmetric DAFC was assembled with Ni4Cu5Fe1/C as both the anode and cathode, with a commercial anion exchange membrane (AEM) as electrolyte. The symmetric DAFC-Ni4Cu5Fe1/C showed a maximum current density of 67 mA cm −2 at 80 °C. To the best of our knowledge, this is the first report on a symmetric DAFC. This work not only reports a new AOR/ORR bifunctional catalyst, but also moves towards the development of low-cost DAFCs with simple structure.